Monitoring blood cholinesterase activity of farmworkers : in vitro inhibition by diphenhydramine and carbaryl - Mohammed, Ammar Ahmed; Mohammad, Fouad Kasim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Plasma and erythrocyte cholinesterase (ChE) activities of male farm workers exposed to pesticides during their routine work were lower than those of unexposed control subjects by 14 and 4%, respectively. Diphenhydramine and Carbaryl inhibited plasma and erythrocyte ChE activities in vitro in pesticide-exposed and unexposed subjects. The percentages of in vitro ChE inhibition induced by carbaryl in the plasma and erythrocytes of unexposed controls ranged between 47-85% and 19-47%, respectively, whereas they were 35-60% and 3-12% in the pesticide-exposed group, respectively. In vitro pretreatment of plasma and erythrocyte ChE with diphenhydramine (20 μM) significantly reduced the inhibitory effect of carbaryl (10 μM) on them by 18% and 10%, respectively. In conclusion, subjects exposed to pesticides during their routine work in agriculture are at risk of reduced blood ChE activity. Diphenhydramine appeared to partially protect blood ChE in vitro from additional carbaryl-induced enzyme inhibition in both pesticide-exposed and unexposed subjects.